1996
DOI: 10.1523/jneurosci.16-21-07021.1996
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Steroid Regulation of Tryptophan Hydroxylase mRNA Expression in Rhesus Macaques

Abstract: Progesterone (P) stimulates prolactin secretion through an unknown neural mechanism in estrogen (E)-primed female monkeys. Serotonin is a stimulatory neurotransmitter in prolactin regulation, and this laboratory has shown previously that E induces progestin receptors (PR) in serotonin neurons. Therefore, we questioned whether E and/or EϩP increased serotonin neural function. The expression of mRNA for tryptophan hydroxylase (TPH) was examined in ovariectomized (spayed) control, E-treated (28 d), and EϩP-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(116 citation statements)
references
References 52 publications
4
110
0
2
Order By: Relevance
“…There was no difference in TPH protein between groups treated with estrogen alone or estrogen þ progesterone. This confirms our earlier observation with additional animals (Pecins- Thompson et al, 1996). In addition, there was no significant difference in the signal corresponding to phosphorylated TPH (Figure 4, bottom) nor in the calculated ratio of phosphorylated TPH to TPH protein (data not illustrated).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…There was no difference in TPH protein between groups treated with estrogen alone or estrogen þ progesterone. This confirms our earlier observation with additional animals (Pecins- Thompson et al, 1996). In addition, there was no significant difference in the signal corresponding to phosphorylated TPH (Figure 4, bottom) nor in the calculated ratio of phosphorylated TPH to TPH protein (data not illustrated).…”
Section: Resultssupporting
confidence: 91%
“…Commercially available antibodies do not discriminate between the translated proteins and provide an indication of total TPH. We demonstrated that 1 month (mo) of estrogen, with or without supplemental progesterone, increased TPH-1 mRNA levels in the dorsal raphe of macaques (Pecins-Thompson et al, 1996). Recently, we have found that TPH-2 is regulated in a similar manner (unpublished).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…7,[21][22][23][24][25][26][27][28][29][30] While these studies demonstrated hormonal regulation of serotonin synthesis, the existence of TPH isoforms was not yet appreciated and therefore not studied. With the identification of TPH2, 4 it has become important to understand the effects of hormones on the individual isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…Buffet et al, 2001) have verified that the concentrations and ratios of circulating sex hormones oscillate throughout the menstrual cycle and influence the central nervous system (CNS) in a large number of varied ways the menstrual cycle effects reported here may be related to hormonal influences. Cholinergic (Gibbs et al, 1998;Lucey et al, 1991;Tseng et al, 1997), glutamatergic (Gazzaley et al, 1996 andWoolley et al, 1997), GABAergic (Murphy et al, 1998), serotonergic (Biegon et al, 1983;Moses et al, 2000;Pecins-Thompson et al, 1996;Sumner and Fink, 1997) noradrenergic (Tseng et al, 1997), and dopaminergic neurotransmitter (Pasqualini et al, 1995) and (Pasqualini et al, 1996) systems all respond to sex hormones. Dopamine is of particular interest here given its role in both response inhibition (Hester et al, 2004) and the ACC error response (Holroyd and Coles, 2002).…”
Section: Discussionmentioning
confidence: 99%